1966
DOI: 10.1042/bj1000095
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of reduced glutathione by subcellular fractions of rat liver

Abstract: 1. A new method was used to diminish the autoxidation of GSH. 2. The oxidation of GSH by liver homogenates was studied with regard to concentration of homogenate, concentration of GSH, time, pH and anaerobiosis. 3. GSH was oxidized by recombinations of the supernatant with microsomes and with mitochondria. Each fraction alone caused little oxidation. 4. Proteins in the supernatant were required to obtain the effect, and low-molecular-weight compounds in the same fraction increased its effect. 5. GSH diminished… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

1968
1968
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 21 publications
1
8
0
2
Order By: Relevance
“…They reported that GPx activities in plasma and erythrocytes did not di¡er signi¢cantly between a group of cattle naturally infected with T. annulata and treated with buparvaquone and another group of uninfected, untreated controls. However, the signi¢cant rise in GPx activity in our study could be due to the fact that GPx appeared to be the major mechanism for intracellular decomposition of lipid peroxides (Christophersen, 1966;Flohe, 1971). Hafeman and colleagues (1974) also proposed that GPx played a crucial role in preventing membranes from peroxide damage induced by lipid peroxides.…”
Section: Discussionmentioning
confidence: 69%
“…They reported that GPx activities in plasma and erythrocytes did not di¡er signi¢cantly between a group of cattle naturally infected with T. annulata and treated with buparvaquone and another group of uninfected, untreated controls. However, the signi¢cant rise in GPx activity in our study could be due to the fact that GPx appeared to be the major mechanism for intracellular decomposition of lipid peroxides (Christophersen, 1966;Flohe, 1971). Hafeman and colleagues (1974) also proposed that GPx played a crucial role in preventing membranes from peroxide damage induced by lipid peroxides.…”
Section: Discussionmentioning
confidence: 69%
“…Low G6PD activity can be followed by reduced activities of SOD and GSH-PX, because of the dependence of the activity of these enzymes on NADPH'H levels in the cell. Christophersen (1966), Flohe (1971) and Hafeman et al (1974) also proposed that GSH-PX played a crucial role in preventing membranes from peroxide damage induced by lipid peroxides. Reduced glutathione is required for the disposal of hydrogen peroxide (H 2 O 2 ) from erythrocytes by a reaction catalysed by GSH-PX.…”
Section: Free Radicals and Blood Parasitesmentioning
confidence: 99%
“…This was accompanied by a modest or no increase in GSSG. Conversion of GSH into GSSG takes place during lipid peroxidation largely through the action of glutathione peroxidase in the presence of lipid hydroperoxides (26). We might infer from these data that glutathione peroxidase activity is low in hepatomas.…”
Section: Resultsmentioning
confidence: 90%
“…GP transforms GSH into GSSG in the presence of lipid hydroperoxides, nucleotide peroxides or hydrogen peroxide. It is thought that this step is important in the destruction of free radicals in damaged tissues (26). GR reduces GSSG back to GSH in the presence of NADPH.…”
Section: Resultsmentioning
confidence: 99%